2018
DOI: 10.4072/rbp.2018.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Ophiomorpha nodosa em sedimentos pleistocênicos da Planície Costeira da Pinheira, Santa Catarina, Brasil

Abstract: Occurrence of Ophiomorpha nodosa in Pleistocene sediments of Coastal Plain of Pinheira, Santa Catarina, Brazil. The occurrence of Pleistocene (MIS) 5 marine ichnofossils in a locality of the Coastal Plain of Pinheira, State of Santa Catarina is described, and their value as indicators of the geological/stratigraphical evolution in this area is discussed. This sedimentary sequence indicates the transition among the subtidal zone, where the ichnofossils occur, to the supratidal zone, and finally to dunes. The ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Ichnotaxonomic identifications of the ex situ specimens were based on the literature (e.g., Kennedy and MacDougall, 1969; Frey et al, 1978; Griffis and Suchanek, 1991; Nickell and Atkinson, 1995; Bromley and Edkale, 1998; Bertling et al, 2006; Gibert et al, 2006; Uchman, 2009; Netto et al, 2012, 2017; Angulo and Souza, 2014; Martins et al, 2018; Rindsberg, 2018), as well as direct comparison with the materials found in situ in the Chuí Formation cropping out at Osório, Santa Vitória do Palmar, and Chuí municipalities (Rio Grande do Sul, Brazil). Ophiomorpha nodosa specimens from the Chuí Formation housed at the Laboratório de História da Vida e da Terra, Universidade do Vale do Rio dos Sinos (LAVIGEA-UNISINOS; N = 8), and Laboratório de Geologia e Paleontologia, Universidade Federal do Rio Grande (LGP-FURG; N = 3) were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ichnotaxonomic identifications of the ex situ specimens were based on the literature (e.g., Kennedy and MacDougall, 1969; Frey et al, 1978; Griffis and Suchanek, 1991; Nickell and Atkinson, 1995; Bromley and Edkale, 1998; Bertling et al, 2006; Gibert et al, 2006; Uchman, 2009; Netto et al, 2012, 2017; Angulo and Souza, 2014; Martins et al, 2018; Rindsberg, 2018), as well as direct comparison with the materials found in situ in the Chuí Formation cropping out at Osório, Santa Vitória do Palmar, and Chuí municipalities (Rio Grande do Sul, Brazil). Ophiomorpha nodosa specimens from the Chuí Formation housed at the Laboratório de História da Vida e da Terra, Universidade do Vale do Rio dos Sinos (LAVIGEA-UNISINOS; N = 8), and Laboratório de Geologia e Paleontologia, Universidade Federal do Rio Grande (LGP-FURG; N = 3) were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…More particularly, Ophiomorpha can serve as a proxy for paleoshorelines (Hyžný et al, 2018) and, consequently, of sea-level changes. In situ Ophiomorpha have been reported in distinct geological units of Brazil (Rossetti et al, 2000;Gingras et al, 2002;Netto and Rossetti, 2003;Tognoli and Netto, 2003;Rossetti and Góes, 2009;Martins et al, 2018). In the particular case of the Rio Grande do Sul Coastal Plain (RSCP), Ophiomorpha nodosa Lundgren, 1891 and Ophiomorpha puerilis Gibert et al, 2006 occur in situ in the emerged deposits of the Upper Pleistocene Chuí Formation (Villwock and Tomazelli, 1995;Gibert et al, 2006;Netto et al, 2012Netto et al, , 2017Lopes, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSL MSL -4m Frey et al, 1978Martins et al, 2018 Tidal notch Definition by Antonioli et al, 2015: "Indentations or undercuttings cut into rocky coasts by processes acting in the tidal zone (such as tidal wetting and drying cycles, bioerosion, or mechanical action)".…”
Section: Ophiomorpha Burrowmentioning
confidence: 99%
“…Other elevation measurement methods include differential GPS, metered tape or rod, topographic map, and total station (Figure 2a). Among these, the most accurate technique is differential GPS, used by Tomazelli and Dillenburg (2007) and Martins et al (2018) in Brazil to report the elevations for the maximum height of Ophiomorpa burrows. Differential GPSs were also used by Muhs et al (2012) and Lorscheid et al (2017) in Curaçao and Bonaire, respectively.…”
Section: Positioning and Sea-level Datumsmentioning
confidence: 99%